Checklist and analysis of completeness of the reef fish fauna of the Revillagigedo Archipelago, Mexico - Fourriére, Manon; Reyes-Bonilla, Héctor; Ayala-Bocos, Arturo; Ketchum, James; Chávez-Comparan, Juan Carlos (Zootaxa, 2016)
This paper presents an updated checklist of cartilaginous and bony fishes from the Revillagigedo Archipelago reefs and nearby areas (Tropical Eastern Pacific). To compile this list, we gathered data from field surveys between 1994 and 2015, from an exhaustive literature review, and by consulting museum collections and databases. With these records we estimated the completeness of the local fish inventory using four non-parametric rarefaction methods. We report a total of 389 species in 102 families; 235 of these are reef fish that occur in the Eastern but also in the Central Pacific, and 13 species were identified as endemic to the archipelago. A non-parametric statistical model predicts that the expected number of reef fish present at Revillagigedo should be 244.3 ± 3.2 species, which is 9 species more than the observed richness, and this difference was statistically significant (p = 0.02). That predictive model estimates that about 96% of the total richness of reef fish from the archipelago is known. Comparisons of the completeness of the inventory at Revillagigedo to that reported for the fish fauna of the Eastern Pacific and worldwide, showed that the quality of the sampling effort is remarkably high, in spite of the geographic isolation of the archipelago.